(untitled) - Terry, W. Scott (Boston, 2006)
Terry's (U. of North Carolina, Charlotte) college text covers the basic methods and results of the research on learning and memory, and the relevance of this research to other disciplines. Revisions to the second edition include greater emphasis on the relationship between neuropsychology and learning and memory, and new material on imagination inflation and recovered memory, spatial memory, post- traumatic stress disorder and related effects on memory
Keywords: Learning, Psychology of,Memory; Textbooks,Textbooks